2021
DOI: 10.1007/s11783-021-1407-5
|View full text |Cite
|
Sign up to set email alerts
|

Repercussions of COVID-19 pandemic on solid waste generation and management strategies

Abstract: It has been over ten months since the beginning of the 2019 coronavirus disease (COVID-2019), and its impact on solid waste management, especially medical waste, is becoming clearer. This study systematically reviews the potential influences of the COVID-19 pandemic on medical waste, personal protection equipment waste and municipal solid waste (MSW), and discusses the corresponding measures and policies of solid waste management in typical countries. The results show that the generation of medical waste from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 40 publications
0
52
0
2
Order By: Relevance
“…Sinha et al (2020) also reported that industrial and commercial waste production suffered a decrease due to the slowdown of economic activity, along with a reduction in recycling activities that led to challenges in the collection and disposal of municipal waste. Besides this, the announcement of lockdowns and travel restrictions led to a drop in waste generation, especially in cities with high levels of tourism ( Liang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sinha et al (2020) also reported that industrial and commercial waste production suffered a decrease due to the slowdown of economic activity, along with a reduction in recycling activities that led to challenges in the collection and disposal of municipal waste. Besides this, the announcement of lockdowns and travel restrictions led to a drop in waste generation, especially in cities with high levels of tourism ( Liang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sementara itu, penelitian di luar negeri mayoritas menunjukkan adanya regulasi serupa dengan cara atau prinsip kerja yang tidak berbeda jauh, namun implementasi di lapangan masih belum sepenuhnya berjalan sesuai dengan regulasi. Hal ini menjadi menarik untuk diteliti sebab terjadinya peningkatan limbah medis yang signifikan dari 18% menjadi 425% tidak diimbangi dengan manajemen yang memadai (Liang et al, 2021). Hasil penelitian di beberapa negara di luar negeri seperti benua Asia, Bangladesh, India, China, Nepal, Romania dan Maroko menunjukkan bahwa sebagian besar telah melakukan pengelolaan limbah medis rumah tangga juga belum dilakukan secara maksimal, meskipun terdapat beberapa negara menurut studi Sangkham (2020) bahwa di Thailand telah dilakukan pengelolaan limbah medis rumah tangga dengan cara penyimpnanan limbah medis habis pakai dalam tas Ziplock sebelum dibuang ke tempat sampah dan diangkut ke tempat pembuangan sementara atau akhir.…”
Section: Hasil Dan Pembahasanunclassified
“…1) Pandemic has changed citizens' habits, bringing some waste generation behavioral trends and new challenges. For instance, lockdown measures have led to an increase in the amount of packaging used for the delivery of food, online shopping, and household groceries (Ganguly & Chakraborty, 2021;Kulkarni & Anantharama, 2020;Liang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…9) Scholars argue that the temporary interruption of selective collection and recycling and the relaxation of waste policies during the critical pandemic period may negatively affect the waste system in the post-pandemic scenario. Besides, it is worth mentioning that the pandemic has postponed recycling and plastic waste policies (Liang et al, 2021;Penteado & Castro, 2021).…”
Section: Introductionmentioning
confidence: 99%